Evaluation of hepatitis B vaccine responsiveness in ‎hemodialysis and peritoneal dialysis patients - Farag, Salama Elsayed; Ghonemy, Tarek A.; Soliman, Sameh A.; Bihery, Ahmed (International Journal of Research in Medical Sciences, 2017)
Background: Hepatitis B Virus (HBV) infection is considered as a major cause of liver ‎cirrhosis and hepatocellular carcinoma. Patients with End Stage Renal Disease (ESRD) are a risk group for HBV infection. The vaccine of hepatitis B has ‎been recommended for prevention of HBV infection in ESRD patient ‎especially on renal replacement therapy. Methods: Eighty seven patients with ESRD on peritoneal ‎dialysis and hemodialysis requiring primary hepatitis B vaccination were ‎enrolled in the study. Each of them received 40 µg of recombinant hepatitis B ‎vaccine in a four-dose schedule. Antibody response was determined by the ‎levels of antibodies to the hepatitis B surface antigen (anti-HBs) after last ‎doses of the vaccination schedule. Results: We observed three response patterns to the ‎immunizations in all patients after vaccination, the nonresponders (24.7%) ‎never reached the minimum protective titer of 10 mIU/mL, the poor responders (18.5%) had titers between 10 and 100 mIU/mL, and the good responders (56.8%) had antibody titers above 100 mIU/mL. Despite a reduction in anti-‎HBs over time, the good responders did not become unprotected during the ‎observation period, especially those participants who had titers above 1000 ‎mIU/mL after the initial immunization. Conclusions: We concluded that the immune ‎response of the HBV vaccine was reduced in the HD and PD patients, which ‎need yearly re-evaluation of seroconversion with booster doses of HBV ‎vaccination if needed‎.